Lnk deficiency attenuates the immunosuppressive capacity of MDSCs via ferroptosis to suppress tumor development - Jingwen Zhou; Hui Yin; JiaHua Pan; Rui Yin; Xin Wei; Min Shen; Liangliang Cai; Ziqi Liu; Jie Zhao; Wenyan Chen; Ruoxun Wang; Xinrui Lan; et al. (Cell Death and Disease)
Abstract A subset of immature myeloid cells known as myeloid-derived suppressor cells (MDSCs) play an immunosuppressive role and actively stimulate the growth of tumors. Lymphocyte adaptor protein (Lnk) regulates the development of hematopoietic stem cells and inflammatory CD8+ T cells by inhibiting cytokine signaling. However, it is unclear how Lnk regulates the function of MDSCs during tumorigenesis. Here, using Lnk –/– mice, we showed that Lnk deficiency inhibited tumor growth in an MDSC-dependent manner. Mechanistically, we demonstrated that Lnk deficiency weakened the immunosuppressive effects of MDSCs through ferroptosis. In addition, Lnk deficiency-induced ferroptosis was regulated by the Flt3/STAT1/IRF1/Alox12 axis. Besides, Lnk was more highly expressed in MDSCs from lung cancer patients. Knocking down Lnk in human MDSCs resulted in increased TNF-α and decreased Arg-1 expression. These findings demonstrate that the role of Lnk is vital in the immunosuppressive ability of MDSCs and offers a novel target for cancer treatment.